2021
DOI: 10.3389/fbioe.2021.686362
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Nitphym, a Robust Thermostable Nitrilase From Paraburkholderia phymatum

Abstract: Despite the success of some nitrilases in industrial applications, there is a constant demand to broaden the catalog of these hydrolases, especially robust ones with high operational stability. By using the criteria of thermoresistance to screen a collection of candidate enzymes heterologously expressed in Escherichia coli, the enzyme Nitphym from the mesophilic organism Paraburkholderia phymatum was selected and further characterized. Its quick and efficient purification by heat treatment is of major interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Phylogenetic analysis revealed that formamidases belong to at least two different groups of enzymes, namely the acetamidase/formamidase super family (FmdA-AmdA, Pfam PF03069), which also includes amidohydrolases of acetamide (Draper 1967 ), and the nitrilase family, which is a subfamily of the carbon-hydrogen nitrilase superfamily and hydrolyses various nitriles, producing ammonia and the respective carboxylic acid (Bessonnet et al 2021 ; Teepakorn et al 2021 ). Although both have certain sequence similarities with members of the major amidase families like aliphatic amidases, acylamide aminohydrolases, and nitrilase/cyanide hydratases, these two groups are demarcated (Fig.…”
Section: Formamidase: Phylogeny Enzyme Activity Biochemical and Genet...mentioning
confidence: 99%
“…Phylogenetic analysis revealed that formamidases belong to at least two different groups of enzymes, namely the acetamidase/formamidase super family (FmdA-AmdA, Pfam PF03069), which also includes amidohydrolases of acetamide (Draper 1967 ), and the nitrilase family, which is a subfamily of the carbon-hydrogen nitrilase superfamily and hydrolyses various nitriles, producing ammonia and the respective carboxylic acid (Bessonnet et al 2021 ; Teepakorn et al 2021 ). Although both have certain sequence similarities with members of the major amidase families like aliphatic amidases, acylamide aminohydrolases, and nitrilase/cyanide hydratases, these two groups are demarcated (Fig.…”
Section: Formamidase: Phylogeny Enzyme Activity Biochemical and Genet...mentioning
confidence: 99%